2002
DOI: 10.1007/s00134-002-1323-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Datex-Ohmeda M-COVX metabolic monitor and the Deltatrac II in mechanically ventilated patients

Abstract: The M-COVX is a suitable integrated device for measuring metabolic gas exchange in ventilated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 15 publications
0
45
1
3
Order By: Relevance
“…Entretanto, tecnologias similares parecem não diferir na acurácia da determinação dos parâmetros (McLellan et al, 2002).…”
Section: Resultsunclassified
“…Entretanto, tecnologias similares parecem não diferir na acurácia da determinação dos parâmetros (McLellan et al, 2002).…”
Section: Resultsunclassified
“…This is because the majority of these formulas are based almost exclusively on weight and height, and in some cases they have not been designed for or validated in children, and, in particular, they do not take into account other factors that could affect EE, such as the type and severity of the disease (6,9,10,16,19) .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to evaluate this monitor during routine clinical use. The M-COVX module has been previously compared with Deltatrac TM a wellvalidated metabolic monitor, under controlled steadystate conditions [18]. This comparison showed that the M-COVX had acceptable agreement with the Deltatrac TM and may be more reproducible at higher inspired oxygen concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…By deriving VO 2 from inspired volumes, the measurements are less affected by leaks and incorrect assumptions about exhaled air temperature and humidity. We have previously described the mode of action of the system in detail [18]. The manufacturers quote the accuracy of the M-COVX module as ±10% up to an F I O 2 of 0.65.…”
Section: Apparatusmentioning
confidence: 99%